(untitled) (Discourse of Law and Administration, 2024)
International legal acts do not in principle prohibit extradition. They regulate and standardize extradition procedures also allow - under certain conditions - the procedures to be prolonged extradition or refusal to extradite the perpetrator. Their impact on the Polish legal system is important because European extradition regulations forced a change to the Constitution of the Republic of Poland.